The Contribution of Decreased Muscle Size to Muscle Weakness in Children With Spastic Cerebral Palsy - Hanssen, Britta; Peeters, Nicky; Vandekerckhove, Ines; De Beukelaer, Nathalie; Bar-On, Lynn; Molenaers, Guy; Van Campenhout, Anja; Degelaen, Marc; Van den Broeck, Christine; Calders, Patrick; Desloovere, Kaat (Frontiers in Neurology, 2021)
Muscle weakness is a common clinical symptom in children with spastic cerebral palsy (SCP). It is caused by impaired neural ability and altered intrinsic capacity of the muscles. To define the con-tribution of decreased muscle size to muscle weakness, two cohorts were recruited in this cross-sectional investigation: 53 children with SCP (median age 8.2 (IQR 4.1) years, 19/34 uni/bilateral) and 31 children with a typical development (TD) (median age 9.7 (IQR 2.9) years). Muscle volume (MV) and muscle belly length for m. rectus femoris, semitendinosus, gastrocnemius medialis and tibialis anterior were defined from three-dimensional freehand ultrasound acquisitions. A fixed dy-namometer was used to assess maximal voluntary isometric contractions for knee extension, knee flexion, plantar flexion, and dorsiflexion from which maximal joint torque (MJT) was calculated. Selective motor control (SMC) was assessed on a 5-point scale for the children with SCP. First, the anthropometrics, strength, and muscle size parameters were compared between the cohorts. Signifi-cant differences for all muscle size and strength parameters were found (p≤0.003), except for joint torque per MV for the plantar flexors. Secondly, the associations of anthropometrics, muscle size, gross motor function classification system (GMFCS) level and SMC with MJT were investigated using univariate and stepwise multiple linear regressions. The associations of MJT with growth-related parameters like age, weight and height appeared strongest in the TD cohort, whereas for the SCP cohort, these associations were accompanied by associations with SMC and GMFCS. The stepwise regression models resulted in ranges of explained variance in MJT from 29.3 to 66.3% in the TD cohort and from 16.8 to 60.1% in the SCP cohort. Finally, the MJT deficit observed in the SCP cohort was further investigated using the TD regression equations to estimate norm MJT based on an anthropometric measure and potential MJT based on MV. From the total MJT deficit, 22.6 to 57.3% could be explained by deficits in MV. This investigation confirmed the disproportional de-crease of muscle size and muscle strength around the knee and ankle joint in children with SCP, but also highlighted the large variability in the contribution of muscle size to muscle weakness.